Evaluation of sterilisation methods for bio-ink components: gelatin, gelatin methacryloyl, hyaluronic acid and hyaluronic acid methacryloyl. (3rd April 2019) - O'Connell, Cathal D; Onofrillo, Carmine; Duchi, Serena; Li, Xin; Zhang, Yifan; Tian, Peilin; Lu, Lanyita; Trengove, Anna; Quigley, Anita; Gambhir, Sanjeev; Khansari, Afsaneh; Mladenovska, Tajanka; et al.
Abstract: Reliable and scalable sterilisation of hydrogels is critical to the clinical translation of many biofabrication approaches, such as extrusion-based 3D bioprinting of cell-laden bio-inks. However sterilisation methods can be destructive, and may have detrimental effects on the naturally-derived hydrogels that constitute much of the bio-ink palette. Determining effective sterilisation methods requires detailed analysis of the effects of sterilisation on relevant properties such as viscosity, printability and cytocompatibility. Yet there have been no studies specifically exploring the effects of sterilisation on bio-inks to date. In this work, we explored the effects of various sterilisation techniques on four of the most widely used bio-ink components: gelatin, gelatin methacryloyl, hyaluronic acid, and hyaluronic acid methacrylate. Autoclaving was the most destructive sterilisation method, producing large reductions in viscosity and in mechanical properties following crosslinking. Filter sterilisation caused some reduction in rheological properties of GelMA due to removal of higher molecular weight components, but did not affect photocrosslinking. Ethylene oxide (EtO) was the least destructive sterilisation method in terms of rheological properties for all materials, had no detrimental effect on the photocrosslinkable methacrylate/methacrylamide groups, and so was chosen for more detailed examination. In biological analyses, we found that EtO treatment successfully eradicated a bacterial challenge of E. coli, caused no decrease in viability of human mesenchyman stem cells (hMSCs), and had no effect on their rate of proliferation. Finally, we found that EtO-treated hydrogels supported encapsulated hMSCs to differentiate towards the chondrogenic lineage, and to produce new cartilage matrix. Our results bring to light various effects that sterilisation can have on bio-inks, as well as highlighting EtO sterilisation as a method which minimises degradation of properties, while still promoting biological function.